2016
DOI: 10.1371/journal.pone.0159326
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Health Experiences of Children Living with Congenital Heart Defects: Including Patient-Reported Outcomes in a National Cohort Study

Abstract: BackgroundUnderstanding children’s views about living with congenital heart defects (CHDs) is fundamental to supporting their successful participation in daily life, school and peer relationships. As an adjunct to a health and quality of life outcomes questionnaire, we asked school-age children who survived infant heart procedures to describe their experiences of living with CHDs.MethodsIn a UK-wide cohort study, children aged 10 to 14 years with CHDs self-completed postal questionnaires that included an open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…The results of a study showed that parents of children of over 2 years and older have difficulty managing child behavior in terms of the physician-defined limitations and attracting child’s cooperation [ 23 ]. Their children also hate social exclusion because of their sense of belonging to their peers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study showed that parents of children of over 2 years and older have difficulty managing child behavior in terms of the physician-defined limitations and attracting child’s cooperation [ 23 ]. Their children also hate social exclusion because of their sense of belonging to their peers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children's and their families' daily lives are significantly affected by a chronic disease, because it introduces new expectations and limitations that need to be addressed on a daily basis (Marshall, Carter, Rose, & Brotherton, 2009). The interest in health care for young persons with chronic diseases has shifted from medical outcomes such as survival to a greater emphasis on wellbeing, daily life experiences, health status and psychosocial outcomes as an essential construct for capturing health outcomes in children and adolescents (Bratt, Luyckx, Goossens, Budts, & Moons, 2015;Emmanouilidou, Galli-Tsinopoulou, Karavatos, & Nousia-Arvanitakis, 2008;Klatchoian et al, 2008;Knowles et al, 2016).…”
Section: Childhood Chronic Health Conditionsmentioning
confidence: 99%
“…Caring for a child with CHD is a stressful experience for families with an impact on family life at various levels because of the increased burden and responsibilities imposed on these families (Almesned, Al-Akhfash, & Al Mesned, 2013; Wei, Roscigno, Hanson, & Swanson, 2015; Wray et al, 2018; Wray & Maynard, 2006). The majority of previous studies addressing psychosocial aspects and impact of CHD on the daily life of children and family have been conducted in Western countries (Cornett & Simms, 2014; Knowles et al, 2016; Rassart, Luyckx, Goossens, Apers, & Moons, 2014; Shearer, Rempel, Norris, & Magill-Evans, 2013; Sira, Desai, Sullivan, & Hannon, 2014). However, it is important to emphasize that the sociocultural/political context, family dynamics, religion, and health care systems vary across societies, and it is likely that these factors have an impact on well-being and psychosocial issues.…”
mentioning
confidence: 99%
“…Of the six selected studies, the distribution per age was as follows: three utilised patient-reported outcome measures in the adult CHD population, 4,7,8 one was conducted in adolescents and young adults with CHD, 5 one was conducted by parents who were told to report from the child's perspective, 3 one was conducted by children between the ages of 10 and 14, in addition to their parents answering the questionnaire. 6…”
Section: Variations In Patient-reported Outcome Measures and Their Ch...mentioning
confidence: 99%